Molecular characterization, adaptive evolution, and expression analysis of the Toll-like receptor gene family in Fenneropenaeus chinensis - Chen, Lulu; Tang, Dan; Hua, Yuyan; Wang, Xinyu; Li, Yanxuan; Wang, Zhengfei (Frontiers in Ecology and Evolution, 2023)
Global warming is a challenge to animal health because of the increased environmental temperature, with subsequent induction of immune suppression and increased susceptibility to disease during summer. The Toll-like receptor (TLR) family is an essential pattern recognition receptor (PRR) that initiates the innate immune response by sensing conserved molecular patterns of pathogens. However, research on the TLR gene family in decapod crustaceans has been conducted sporadically, without systematic naming, and the relationship between pathogen immunity adaptation and adaptive evolution of immune-related genes is unclear. In this study, various TLR gene sequences in decapod crustaceans were collected, and the unified name of Fenneropenaeus chinensis was confirmed using sequence alignment. Structural characteristics and evolutionary analyses of TLR genes in decapod crustaceans were performed, and ten FcTLR genes were identified in F. chinensis. Protein domain analysis revealed that FcTLR proteins contain 4-25 LRR domains used to recognize different pathogens. Selection pressure analysis revealed that TLR1 and TLR9 were subjected to positive selection pressure in decapod crustaceans, which may be related to their resistance to environmental changes. Furthermore, the expression of ten TLR genes was detected in F. chinensis following white spot syndrome virus (WSSV) infection. The results demonstrated that FcTLR1, FcTLR7, and FcTLR9 responded positively, which was also consistent with the results of the protein domain and selection pressure analyses. This study provides new insights into the immune response and adaptive evolution of TLRs in decapod crustaceans to prevent environmental damage, such as pathogens and high temperature.